3D printing-assisted nanoimprinting of hyaluronic acid/chitosan interpolymer complex hydrogels for guiding cell growth - Young-Qi Xu; Peng-Chin Tsai; Kun-Liang Hsieh; Ming-Chia Li (Carbohydrate Polymer Technologies and Applications)
The synergy of hydrogels and rapid prototyping technologies offers potential in tissue engineering scaffolds. Hydrogels are promising for soft and hard tissue regeneration but face challenges in shaping and maintaining geometric integrity due to weak mechanical strength during post-swelling. This study develops an interpolymer complex (IPC) hydrogel using HA/CHI polysaccharides for bioengineered skin equivalents, integrating 3D printing and nanoimprinting technologies. The IPC hydrogel is printed on commercial CD and DVD discs, which serve as stampers to create grooved topographies. Scanning Electron Microscopy (SEM) observations reveal that the application of 3D printing-assisted nanoimprinting techniques to IPC hydrogels facilitates large-scale and uniform grooved surface topographies. This design, using the lotus effect to minimize swelling, preserves the nanoimprinted topography during cell culture. Furthermore, our results showed that the grooved topography can guide mouse fibroblasts (mFB), human foreskin (BJ), and human smooth muscle (SMC) cells to directional growth on the IPC membrane with groove structures. Our experimental findings during the wound healing process indicate that an IPC membrane with a CD grooved surface is more conducive to cell proliferation and is more effective as a dressing for wound healing applications.